Clinical Significance of BCL2, C-MYC, and BCL6 Genetic Abnormalities, Epstein-Barr Virus Infection, CD5 Protein Expression, Germinal Center B Cell/Non-Germinal Center B-Cell Subtypes, Co-expression of MYC/BCL2 Proteins and Co-expression of MYC/BCL2/BCL6 Proteins in Diffuse Large B-Cell Lymphoma : A Clinical and Pathological Correlation Study of 120 Patients - Kuan, Jew-Win; Ting, Choo Yuen; Chang, K. M.; Jameela, Sathar; Chew, Lee Ping; Wong, Jacqueline Oy-Leng; Yusri, Yusuf; Lily, Wong; Ahmad Toha, Samsudin; Mohd Nurjaya, Bin Mohd Pana; Lee, Suk Kam; Raja Gopal, Navarasi S.; et al. (Ivyspring International Publisher, 2019)
Background: Clinical significance of germinal center B-cell (GCB) and non-GCB sub-categorization, expression of MYC, BCL2, BCL6, CD5 proteins and Epstein Barr virus encoded RNA (EBER) positivity in diffuse large B-cell lymphoma (DLBCL) remain controversial. Could these biomarkers accurately identify high risk DLBCL patients? Are MYC, BCL2 and BCL6 proteins expression feasible as baseline testing to predict c-Myc, BCL2 or BCL6 gene rearrangements? Aims: To investigate prognostic values of GCB/non-GCB sub-categorization, Double Protein Expression Lymphoma (DPL), Triple Protein Expression Lymphoma (TPL), positivity of CD5 protein and EBER in patients with DLBCL disease. To evaluate correlation between BCL2 , c-Myc and BCL6 gene rearrangements with BCL2, MYC and BCL6 proteins expression. Methods: Diagnostic tissue samples of 120 DLBCL patients between January 2012 to December 2013 from four major hospitals in Malaysia were selected. Samples were subjected to immunohistochemical staining, fluorescent in-situ hybridization (FISH) testing, and central pathological review. Pathological data were correlated with clinical characteristics and treatment outcome. Results: A total of 120 cases were analysed. Mean age of diagnosis was 54.1 years ± 14.6, 64 were males, 56 were females, mean follow up period was 25 months (ranged from 1 to 36 months). Of the 120 cases, 74.2% were non-GCB whereas 25.8% were GCB, 6.7% were EBER positive, 6.7% expressed CD5 protein, 13.3% were DPL and 40% were TPL. The prevalence of c-Myc, BCL2, BCL6 gene rearrangements were 5.8%, 5.8%, and 14.2%, respectively; and 1.6% were Double Hit Lymphoma (DHL). EBER positivity, DPL, TPL, c-Myc gene rearrangement, BCL2 gene rearrangement, extra copies of BCL2 gene and BCL6 gene rearrangement were associated with shorter median overall survival (P<0.05). IPI score was the significant determinants of median overall survival in DPL and TPL (P<0.05). CD5 protein expression and GCB/non-GCB sub-categorization did not affect treatment outcome (P>0.05). Overall, c-Myc, BCL2 and BCL6 gene rearrangements showed weak correlation with expression of MYC, BCL2 and BCL6 proteins (P>0.05). Fluorescent in situ hybridization is the preferred technique for prediction of treatment outcome in DLBCL patients. Conclusion: c-Myc, BCL2, and BCL6 gene rearrangements, EBER expression, DHL, TPL and IPI score are reliable risk stratification tools. MYC, BCL2 and BCL6 proteins expression are not applicable as baseline biomarkers to predict c-Myc, BCL2, and BCL6 gene rearrangements.